2015
DOI: 10.1039/c5py00308c
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and reliable detection of glass transition of polymers by fluorescent probes based on AIE luminogens

Abstract: A sensitive and reliable approach for the detection of the glass transition of polymers using AIE luminogens as fluorescent probes was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 36 publications
2
78
0
Order By: Relevance
“…1,[22][23][24][25][26][27][28][29] In this line, Guan et al designed and synthesized a unique uorescent surfactant (TPE-DTAB), which combined both the properties of the aggregation-induced emission (AIE) and amphilicity which together were used to image the macrodispersion of the layered double hydroxide llers (montmorillonite) in the polymer matrix. 30 Wang's group also visualized the entire gelation process of chitosan (CS) by the synthesized AIE uorogenic probe, that is, tetraphenylethene-labelled chitosan (TPE-CS).…”
Section: 21mentioning
confidence: 99%
“…1,[22][23][24][25][26][27][28][29] In this line, Guan et al designed and synthesized a unique uorescent surfactant (TPE-DTAB), which combined both the properties of the aggregation-induced emission (AIE) and amphilicity which together were used to image the macrodispersion of the layered double hydroxide llers (montmorillonite) in the polymer matrix. 30 Wang's group also visualized the entire gelation process of chitosan (CS) by the synthesized AIE uorogenic probe, that is, tetraphenylethene-labelled chitosan (TPE-CS).…”
Section: 21mentioning
confidence: 99%
“…AIE molecules possess the advantages of high quantum yields in the solid state, good stability at high temperatures, and restricted molecular motions in rigid environments. Recently, the glass transition temperatures of polymers have been successfully investigated by employing AIE molecules as probes . The TPE molecule was doped into the polymer and the fluorescent intensities of the polymer were studied at various temperature ranges.…”
Section: Process Monitoringmentioning
confidence: 99%
“…Recently,t he glass transition temperatureso fp olymers have been successfully investigated by employingA IE molecules as probes. [59] The TPE molecule was doped into the polymer and the fluorescent intensities of the polymer were studied at various temperature ranges.T he fluorescent emission spectra showedc ontinuouslyd ecreasing emissioni ntensity with increasingt emperature. At urning point for the slope can be observed in the curves, which was determined as the glass transition temperature of the polymer.T he mechanism for the fluorescence decrease has been studied.…”
Section: Glass Transition Of Polymersmentioning
confidence: 99%
“…Now, the AIE or AIEE becomes one of the top research fields . Because of the high fluorescence intensity and photoluminescence quantum efficiency caused by the AIE or AIEE effect, AIE luminogens have extensively been applied in various fields, including fluorescent sensors, nonlinear optical applications, cell imaging, light‐emitting diodes (OLEDs), and solar cells . Tian and co‐workers reported a series of conjugated dendrimers with the obvious AIE properties, which possessed markedly large intrinsic two‐photon absorption cross section.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, several kinds of AIE or AIEE small molecules have been developed, such as 1‐methyl‐1,2,3,4,5‐pentaphenylsilole, indolo[3,2‐ b ]carbazolederivatives, V‐shaped polyaromatic amphiphiles, boron diiminates, tetraphenylethene (TPE) derivatives, and so on. Systematic studies have suggested that the restriction of intramolecular rotation (RIR) is the main cause of the AIE or AIEE effect .…”
Section: Introductionmentioning
confidence: 99%